2021
DOI: 10.1111/odi.14086
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine mouthwash reduces the salivary viral load of SARS‐CoV‐2: A randomized clinical trial

Abstract: Objectives This study aimed to evaluate the effect of 0.12% chlorhexidine gluconate on the salivary load of SARS‐CoV‐2. Materials and Methods A randomized, double‐blind, placebo‐controlled trial was performed on 100 participants positive for SARS‐CoV‐2. In the test group (n = 50), volunteers gargled with a mouthwash containing 15 ml of 0.12% chlorhexidine gluconate for 1 min, while the control group (n = 50) used a placebo. Saliva samples were obtained before (baseline) and 5 and 60 min after using the solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 29 publications
1
46
0
2
Order By: Relevance
“…In these studies, rinsing times ranged between 30 s and 1 min. In the placebo group, distilled water [ 14 , 22 , 23 , 24 , 25 ], saline [ 26 ], and an unspecified inactive substance [ 27 ] were used. The control group in one study did not receive treatment [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In these studies, rinsing times ranged between 30 s and 1 min. In the placebo group, distilled water [ 14 , 22 , 23 , 24 , 25 ], saline [ 26 ], and an unspecified inactive substance [ 27 ] were used. The control group in one study did not receive treatment [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The control group in one study did not receive treatment [ 28 ]. In the test group several active compounds were used: CDCM ® (0.1% beta-cyclodextrin and 0.1% Citrox ® ) ( n = 1 [ 14 ]); hydrogen peroxide (HP) at 1% [ 25 , 26 ] or 1.50% [ 22 ]; chlorhexidine (CHX) at 0.12% [ 22 , 25 , 26 , 27 , 28 ] or 0.20% [ 23 , 24 ]; a combination of 0.12% CHX and 1.50% HP [ 22 ]; cetylpyridinium chloride (CPC) 0.07% [ 25 ] and 0.075% [ 23 ]; a combination of 0.075% CPC and 0.28% Zinc (Zn) [ 22 ]; and povidone iodine (PVP-I) at 0.50% [ 23 , 26 ], 1% [ 24 ] and 2% [ 25 ]. All the studies investigated the effect of oral rinses, except for one article [ 28 ] which studied the combination of an oral rinse with an oropharyngeal spray.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are multiple recent RCTs performed evaluating the virucidal activity of CHX against salivary SARS-CoV-2. A study by Costa et al [ 24 ] evaluated the efficacy of 0.12% CHX at 5 and 60 min after rinsing for 1 min. They found that there was a significant reduction (72%) in the salivary load at both 5 and 60 min after rinsing compared with the control.…”
Section: Discussionmentioning
confidence: 99%